KOMPARASI ANIMASI FORMAT LOTTIE, JSON, GIF DAN MP4 DENGAN METODE LOAD TESTING - Wardhani, Diky (Universitas Siber Indonesia, 2024)
The flexibility of the mobile and web platforms allows users to interact better where the animation is applied to a very good user interface design so that users do not feel bored using both platforms. Animations displayed on mobile and web platforms consume storage and bandwidth resources that impact platform performance. This load testing aims to find out how fast the four animation formats are for resource efficiency. This test results in that Lottie format animations can be loaded at a speed of 4.58 ms, JSON format at a speed of 6.62 ms, GIF format at a speed of 15.10 ms and MP4 format at a speed of 95.53 ms. The four animation file formats Lottie and JSON are small, lightweight formats that can be quickly uploaded to a website and resized at will. By using lottie animation and JSON you can reduce storage resources and bandwidth.